Management Planning for Nature Conservation A Theoretical Basis & Practical Guide - Alexander, Mike (Springer Netherlands : Imprint: Springer, 2008)
Mike Alexander's Management Planning for Nature Conservation brings a new dimension to the modern literature on conservation management. Combining key theories with real practice it fills a critical gap which has often hindered in-depth understanding of the planning process. The book provides historical and rational background which helps to explain what makes a really effective management plan, and it presents a detailed practical guide to developing such a plan. It concludes with a series of case studies which clearly illustrate the underlying principles drawn out in the text, while highlighting the different approaches demanded by very different sites. Drawing on the expertise of leaders in both conservation research and wildlife management, and with a combined experience from around the world, this book is essential reading for professional conservation managers and any student studying management planning for conservation within a range of degree and postgraduate courses. The book will be equally important for those attending professional training programmes and courses for practitioners in the statutory and voluntary environment and wildlife conservation sector. Mike Alexander has been at the forefront of developing systems and methods in the field of management planning for conservation, with experience ranging from Uganda to Estonia, and from Costa Rica to Wales. He was a member of the team responsible for developing the current management planning guidelines for the international Ramsar (Convention on Wetlands) sites located around the world.